Application of the Naive Bayes Method in the Classification of Employee Status at PT. Prosperous New Light - Rahmat S, Khaerullah; Kanedi, Indra; Fredricka, Jhoanne (Jurnal Media Computer Science, 2023)
Sinar Baru Makmur In determining the extension of an employee's contract, it is taken from the results of an employee's performance appraisal, if the performance results are good or very good, a contract extension will be carried out. However, in determining the results of employee contract extensions there are still some subjective judgments, and family relationships that create gaps with other employees in determining the final outcome of the assessment. To avoid subjectivity in evaluating employee performance, this study created an application for evaluating employees by classifying them using the Naive Bayes method. Employee status classification application at PT. Sinar Baru Makmur is created using the Visual Basic .Net programming language. The application can help manage employee performance appraisal evaluation data and can also help provide recommendations for the eligibility of employee status whether to be extended or not renewed based on the classification results of the Naive Bayes Method.